Revitalization of urban centers from the perspective of the Main Street program in Barrios Altos - URDANIGUE CONTRERAS, AARON (2018)
The following document aims to present a handful of studies that develop the importance of social actors as one of the groups in charge of the preservation of architectural heritage, especially those involved in traditional commerce. Within this framework, traditional local traders are the actors who are most interested in the revitalization of historical centers. Many institutions, both public and private, currently encourage policies for the development of historical centers, such as the United Nations Educational, Scientific and Cultural Organization (UNESCO). This essay aims to show the revitalization “from within” of Barrios Altos. In this sense, it explains the North American experience from the point of view of the Main Street program, which, since the early 1980s, has been developing successfully in small and medium towns in the United States. This program focuses on the revitalization of commercial areas, usually located around the main street of a town; hence the name. From this perspective, the following investigation seeks to land this program in an area of Barrios Altos, specifically in the monumental urban environment of Cinco Esquinas, one of the most representative spaces, where traditional local commerce is still present and there is patrimonial architecture to be preserved.